2022
DOI: 10.1093/icb/icac141
|View full text |Cite
|
Sign up to set email alerts
|

Help Me, Symbionts, You're My Only Hope: Approaches to Accelerate our Understanding of Coral Holobiont Interactions

Abstract: Tropical corals construct the three-dimensional framework for one of the most diverse ecosystems on the planet, providing habitat to a plethora of species across taxa. However, these ecosystem engineers are facing unprecedented challenges, such as increasing disease prevalence and marine heatwaves associated with anthropogenic global change. As a result, major declines in coral cover and health are being observed across the world's oceans, often due to the breakdown of coral-associated symbioses. Here, we revi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 157 publications
1
15
0
Order By: Relevance
“…This demonstrated how targeted inoculation can successfully shift Symbiodiniaceae community composition toward a higher proportion of heat tolerant strains without thermal treatment (Silverstein et al 2015). Although the longevity of these partnerships is still unclear, these are promising results for future development of in hospite studies on the role of temperature on inter-partner symbiosis dynamics and symbiont recognition mechanisms (Bove et al 2022). The success and potential insights from such experimental approaches will rely on future efforts to establish a variety of coral host-specific Symbiodiniaceae cultures (including the establishment of specific cultures from G. fascicularis) for further study.…”
Section: Symbiosis Reestablishment In Adult Coralsmentioning
confidence: 98%
“…This demonstrated how targeted inoculation can successfully shift Symbiodiniaceae community composition toward a higher proportion of heat tolerant strains without thermal treatment (Silverstein et al 2015). Although the longevity of these partnerships is still unclear, these are promising results for future development of in hospite studies on the role of temperature on inter-partner symbiosis dynamics and symbiont recognition mechanisms (Bove et al 2022). The success and potential insights from such experimental approaches will rely on future efforts to establish a variety of coral host-specific Symbiodiniaceae cultures (including the establishment of specific cultures from G. fascicularis) for further study.…”
Section: Symbiosis Reestablishment In Adult Coralsmentioning
confidence: 98%
“…This demonstrated how targeted inoculation can successfully shift Symbiodiniaceae community composition towards a higher proportion of heat tolerant strains without thermal treatment (Silverstein et al 2015). Although the longevity of these partnerships is still unclear, these are promising results for future development of in hospite studies on the role of temperature on inter-partner symbiosis dynamics and symbiont recognition mechanisms (Bove et al 2022). The success and potential insights from such experimental approaches will rely on future efforts to establish a variety of coral host-specific Symbiodiniaceae cultures (including the establishment of specific cultures from G. fascicularis ) for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of marine microbiome changes due to environmental stressors is provided by metagenomic studies, which have revealed the alteration of core microbial communities in certain sponge species, including Rhopaloeides odorabile , Xestospongia muta , Halichondria bowerbanki and Haliclona cymaeoformis [ 191 , 192 , 193 , 194 ]. Such shifts in the host microbiome in response to environmental stresses can result in the loss of metabolic potentials and dysbiosis, leading to sponge disease and mortality [ 70 , 195 ]. There are currently gaps in our understanding of the effects of environmental perturbance on the production of secondary metabolites by microbial symbionts.…”
Section: Impacts Of Climate Change and Human Activity On Marine Chemi...mentioning
confidence: 99%